HUBUNGAN MOTIVASI KERJA DENGAN KOMITMEN KERJA KARYAWAN DI BALAI PENDIDIKAN DAN PELATIHAN SOSIAL - Fannidia Ifani Putri (Universitas Negeri Padang, 2014)
This study examines thetieswork motivation with employee commitment. The hypothesis of this study were (i) there is a significant relationship between motivation and employee commitment to the level of 95%, (ii) there is no significant relationship between motivation and employee commitment to the level of 95% . Methods of data collection using questionnaires orquestionnaires. The subjects in this study were employees of a company located in Padang. The data obtained, and then analyzed using product moment correlation analysis method. The results of the study proved that there is a significant relationship between work motivation and employee commitment, which work motivation are positively correlated with work commitments. Key Word: Work Motivation, Work Commitments